Multiaxial Fatigue Behavior of High-Density Polyethylene (HDPE) Including Notch Effect: Experiments and Modeling - Amjadi Mohammadreza; Fatemi Ali (MATEC Web of Conferences, 2019)
High-Density Polyethylene (HDPE) is used in many industries with many applications from automotive industry to biomedical implants. It can be manufactured using different processing techniques including compression molding, injection molding, and blow molding. Multiaxial loading and non-proportionality between different loading sources are inevitable in many applications. It is shown that the common multiaxial fatigue criteria such as von Mises equivalent stress are not able to correlate the multiaxial fatigue data. In this study, multiaxial fatigue behavior of neat HDPE is investigated using hollow tubular specimens through experimental fatigue tests. Axial, torsion, and combined in phase and out-of-phase axial-torsion fatigue tests were conducted. Stress concentration effect on multiaxial fatigue behavior was also studied. Experimental results and analytical models used to account for the aforementioned effects are presented and discussed in this paper.